(untitled) (Research, Society and Development, 2022)
Introduction: The advance in the development of implant technologies that are more resistant and more modern, adapting the human anatomy, reducing pain and the readaptation process, in addition to the great improvement of surgical techniques and techniques of sterilization and packaging of surgical materials, made arthroplasty knee (TKA) the most performed group of surgeries in the orthopedic environment. The advancement of techniques in the application of knee trampling has made the technique of frequent and increasing use in the last decade, conditioning its success to several factors: the design of the components, the quality of the available materials, the manufacturing technique, application adequate to each patient, as well as the development of the surgical technique. Methodology: This is a narrative review of the literature. Results: A great instrument is the navigation of total knee arthroplasty, which is an instrument that facilitates the operative performance, also having the ability to assist the surgeon in making intraoperative decisions, enabling the simulation of situations before performing them. It has great use in the teaching field, as it makes it possible to immediately see the effect of each action performed during the operation, and it is possible that the navigator eliminates the need for the surgeon’s qualification or reduces the value of his experience, as the navigator does not point out paths or make decisions. by the surgeon, providing only assistance in obtaining and measuring the planned results for each action. This activity enhances the surgeon’s knowledge and experiences as it provides great parameters with high precision and real-time objectives in the operation. Conclusion: The use of robotics in orthopedic surgery should be seen as an instrument available to the Surgeon, demonstrating their knowledge and never as an autonomous independent system that can compensate for an eventual deficiency of experience or knowledge. Important studies reveal that using robotics, surgery revision rates have decreased, increasing patient satisfaction with the surgery.